A biomimetic hierarchical structure with a hydrophilic surface and a hydrophobic subsurface constructed from waterborne polyurethanes containing a self-assembling peptide extender. Issue 26 (21st June 2018) - Zhang, Fanjun; Wang, Rong; He, Yuanyuan; Lin, Weiwei; Li, Yuxi; Shao, Yiqi; Li, Jiehua; Ding, Mingming; Luo, Feng; Tan, Hong; Fu, Qiang
Abstract : A biomimetic hierarchical structure with a hydrophilic surface and a hydrophobic subsurface is constructed from waterborne polyurethanes. Abstract : Constructing a biomimetic hierarchical structure is of great benefit to achieve materials with expected high performance. In this work, a new Fmoc-diphenylalanine (Fmoc-FF) based peptide extender (PPE) is synthesized for preparing a series of waterborne polyurethanes (WPUs) to construct a hydrophilic surface and a hydrophobic subsurface. A pre-assembly structure of the WPU emulsion particle is achieved by the introduction of PPE. It possesses a compact core consisting of hydrophobic segments of Fmoc-FF with π–π stacking and a loose shell consisting of hydrophilic polyethylene glycol (PEG) segments. The self-assembled Fmoc-FF could also enhance the phase separation between soft segments and hard segments. During film formation by demulsification, the outer PEG segments easily migrate onto the surface and the hydrophobic compact cores aggregate into the subsurface. Such an architecture endows WPU films with simultaneous biocompatibility, antifouling ability, and water resistance under wet conditions. This work provides a new insight into the design of a polymer emulsion with a pre-assembled phase to construct the expected hierarchical structure of films or coatings for biomaterials and antifouling materials.